Analisis Pertanggungjawaban Hukum Findaya Terhadap Pemberi Pinjaman Apabila Penerima Pinjaman GoPay Pinjam Wanprestasi (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the position of Findaya in the implementation of GoPay Pinjam services, as well as to examine the legal liability for Findaya against the Lender in the event that the Lender breach of contract. This study uses a normative legal research method with a statutory approach and a conceptual approach. The data collection method used is a literature study sourced from primary legal materials and secondary legal materials. The inference method used is deductive logic technique. The results of this study indicate that in the GoPay Pinjam service which is Peer to Peer Lending, Findaya plays a role as a loan organizer as well as a power of attorney for the Lender. Its position is as an intermediary between the Lender and the Loan Recipient. Furthermore, in the event of default in the form of default by the Borrower, Findaya does not bear the risk of default but has a responsibility based on Article 2.3 of the General Conditions of Use of GoPay Pinjam to seek dispute resolution to fulfill the rights and protect the interests of the Lender.